ANALISIS MAJAS PADA NOVEL “DIA ADALAH DILANKU TAHUN 1990” KARYA PIDI BAIQ - Rima Mardiah; Siti Rosidah; Restu Bias Primandhika (IKIP Siliwangi, 2018)
The problems discussed in this study, namely: 1) What kinds of subjects are contained in the novel He is in my 1990s? 2) What method is used in this study? 3) How is the study of the majors contained in the novel He Is My Left in 1990 ?. This study aims to make the reader get a certain effect on the style of language which tends to refer to several types of lectures such as the majors of Anaphora, Hyperbole, Association, Personification, Rhetoric, Metonymy, Synesthesia, and Antithetics. This study uses the stylistic method, which is knowledge related to style and style of language and refers more to language style. The results of the stylistic analysis of the novel He is My Left in 1990 indicate that the novel contained various princes. The conclusion of this study is that the novel He is My Left in 1990 is in 3 majors, namely the comparison, the repetition and the contradiction. After being analyzed from all the majors, among others, such as the comparison ratio consisting of: hyperbole, metonymy, epithet, personification, synesthesia, association and simile. Repetition majors consist of: pleonasm, epizeukis, anadiplosis, mesodiplosis, and anaphora. The principle of the conflict consists of: contra interminist diction.